2011
DOI: 10.1186/1756-0500-4-65
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of anatid and galliform microsatellite markers to the genetic diversity studies of domestic geese (Anser anser domesticus) through the genotyping of the endangered zatorska breed

Abstract: BackgroundThe lack of a sufficient number of molecular markers seriously limits the cognition of genetic relationships within and between populations of many species. Likewise, the genetic diversity of domestic goose (Anser anser domesticus), with a great number of breeds throughout the world, remains poorly understood at the molecular level.FindingsThirty-five goose, seventeen duck and eight chicken microsatellite primer pairs were screened for their utility in the cross-species amplification on DNA from 96 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…The observed heterozygosity over all loci was similar or lower than mean expected. The mean observed heterozygosity in Tesedik Goose was similar as in other European geese (Aliczki et al, 2007;Andres and Kapkowska, 2011;Noreikiene et al, 2012), but higher than in Suchovska and Slovak Goose breeds (Mindek et al, 2014).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…The observed heterozygosity over all loci was similar or lower than mean expected. The mean observed heterozygosity in Tesedik Goose was similar as in other European geese (Aliczki et al, 2007;Andres and Kapkowska, 2011;Noreikiene et al, 2012), but higher than in Suchovska and Slovak Goose breeds (Mindek et al, 2014).…”
Section: Resultssupporting
confidence: 76%
“…All estimated microsatellite loci were polymorphic as was published in previously studies (Aliczki 2007;Weiß et al 2008;Andres and Kapkowska, 2011), with a varying number of alleles and expect for Aalμ1 used in diversity study were suitable according to number of detected loci over the population. The number of alleles detected in loci TTUCG5, CKW21, Bcaμ1 was similar as in Zatorska breed (Andres and Kapkowska, 2011). Considerable lower number of detected alleles were in CKW21, Aalμ1, Ans2 and Ans25 loci, compare to other published papers (Liu et al, 2006;Aliczki 2007;Weiß et al 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant deficiency of heterozygotes occurred in locus TTUGC5 (Slovak), Ans2 (Slovak) and Bcaμ1 (Suchovska, Tesedik), (Table 3). Liu et al, 2006;Aliczki 2007;Wieß et al 2008;Andres and Kapkowska, 2011). Barker (1994) suggested that microsatellite loci used in genetic distance studies should have more than four alleles in order to reduce the distance estimate standard error.…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly accepted that PIC values > 0.50 are characteristic of the most useful markers, 0.25 < PIC > 0.50 of those moderately informative, and PIC < 0.25 of the less informative (Andres and Kapkowska, 2011). Thus, the loci optimized in this study can thus be considered moderate to highly informative.…”
Section: Resultsmentioning
confidence: 99%